Connecting Māori Youth and Landscape Architecture Students through Participatory Design. Issue 2 (2nd April 2020) - Rodgers, Maria; Marques, B.; McIntosh, J.
Abstract: As with many Indigenous cultures, the Māori connection to the land in Aotearoa New Zealand has been weakened by colonization, urbanization and other factors. In particular, Māori youth in their progressively technological world, experience a disconnection from their culture and their land (whenua). Using a participatory design method and designing with the land is proposed as a way to enable cultural reconnection through the reconstruction of identity. Developing ideas from community engagement and place-making with Indigenous groups, in this research landscape architecture students joined with Māori youth (rangatahi) attending an alternative education program to co-design a public community space. The article reflects on the benefits of the community-based participatory research methodology for both groups, including the development of an understanding of the importance of Indigenous knowledge and rebuilding connection to culture and land.